2003
DOI: 10.1002/iroh.200390022
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Vertical Distribution of the Phytobenthic Community within a Pool and Riffle Sequence of an Alpine Gravel Stream

Abstract: In the 2 nd order mountain brook "Oberer Seebach" (Austria), diatoms and cyanoprokaryotes dominate the microphytobenthos, with the diatoms forming the richest species group.Comparative investigations of different habitats clearly show seasonal variations in algal species composition and biomass throughout the year. Pool habitats hold a higher number of taxa than riffle sites. In addition, phytobiomass is two-to nearly fourfold higher in pools. Based on investigations of the chlorophyll-a vertical profiles with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Cyanobacteria can be abundant components of benthic biofilms [43] and they are well known for allelopathy as a competitive strategy [46]. The spatial variation of cyanobacterial abundance throughout our study streams may therefore further contribute to the network scale pattern of alpha diversity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cyanobacteria can be abundant components of benthic biofilms [43] and they are well known for allelopathy as a competitive strategy [46]. The spatial variation of cyanobacterial abundance throughout our study streams may therefore further contribute to the network scale pattern of alpha diversity.…”
Section: Discussionmentioning
confidence: 98%
“…As streambed geomorphology can influence benthic biofilm communities [24,43], we tested whether physical changes (e.g. water depth, velocity, channel slope or Froude number) explain the observed drop in alpha diversity and evenness across confluences.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack or paucity of primary production in the subsubstratum (Mu¨llner & Schagerl, 2003), invertebrates probably feed on detritus and biofilms derived mainly from allochthonous inputs and on the associated microflora: fine particulate organic matter sustains a high number of collectorgatherers while coarse organic matter attracts shredders. We found that some large shredders (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…due to the calcareous geology of the catchment, and stream water is saturated in oxygen even down to 2 m in the streambed. Photosynthetically active radiation (PAR) can be seasonally high, allowing benthic diatoms and cyanophytes to develop notable biomass [Müllner and Schagerl, 2003] (Figure 1b). …”
mentioning
confidence: 99%